SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SANTA PERAWAN MARIA SEBAGAI MODEL MENURUT SAN - Tibo, Paulinus (IN VERITATE LUX, 2020)
The Church's teaching that presents Mary more specifically as a model in Divine worship is Marialis Cultus. This apostolic letter recommended by Pope Paul VI on February 2 1974 aims to promote respect for the Blessed Virgin Mary, especially in Divine worship. In Marialis Cultus the virtues of the Blessed Virgin Mary are clearly displayed, namely humility shown by listening to God's Word and implementing it, always praying and conveying her hopes to God. Mary is also called a virgin because of her obedience and faith, her absolute (total) trust in God. The Church sees that the actual situation experienced by the people is really worrying, for example: The people have not opened themselves fully to God, humility has not really been realized so that some people have not listened to the word and carried it out, or listened only in the mind and not in the heart, praying only just pray without effort and perseverance. Worship cannot be separated from the reality of life, and vice versa, life cannot be separated from worship. So one solution to answer this kind of situation of the people is the people's catechesis about Mary which is based on the Marialis Cultus document.